Discovery of a New Xanthone against Glioma: Synthesis and Development of (Pro)liposome Formulations - Alves, Ana (2020)
Following our previous work on the antitumor activity of acetylated flavonosides, a new acetylated xanthonoside, 3,6-bis(2,3,4,6-tetra-O-acetyl-β-glucopyranosyl)xanthone (2), was synthesized and discovered as a potent inhibitor of tumor cell growth. The synthesis involved the glycosylation of 3,6-di-hydroxyxanthone (1) with acetobromo-α-d-glucose. Glycosylation with silver carbonate decreased the amount of glucose donor needed, comparative to the biphasic glycosylation. Xanthone 2 showed a potent anti-growth activity, with GI50 < 1 μM, in human cell lines of breast, lung, and glioblastoma cancers. Current treatment for invasive brain glioma is still inadequate and new agents against glioblastoma with high brain permeability are urgently needed. To overcome these issues, xanthone 2 was encapsulated in a liposome. To increase the well-known low stability of these drug carriers, a proliposome formulation was developed using the spray drying method. Both formulations were characterized and compared regarding three months stability and in vitro anti-growth activity. While the proliposome formulation showed significantly higher stability, it was at the expense of losing its biocompatibility as a drug carrier in higher concentrations. More importantly, the new xanthone 2 was still able to inhibit the growth of glioblastoma cells after liposome formulation.